Core Competencies in Disaster Nursing among Nurses at a General Hospital in Coastal Areas - Bahlail, Rezka; Somantri, Irman; Mulya, Adelse Prima (Universitas Muhammadiyah Semarang, 2024)
Indonesia is known as a country with a high risk of natural disasters. Nurses as the main element in health care, hold an important role in disaster management. Therefore, nurses who are competent in disaster management are needed. This study aimed to describe core competencies in disaster nursing in facing natural disasters among nurses in a general hospital that is located near the coastal areas. A descriptive quantitative research method was used in this study. Samples were recruited using the simple random sampling technique. The data were collected using DNCCS and analyzed using univariate data analysis. 120 nurses who participated in this study had a higher score (mean = 246.52). Uniquely, nurses who had parcipated in disaster training actually had a lower score (mean = 246.43). In contrast to nurses who had participated in disaster volunteering, they had a higher score overall even though they were small (n=25). Overall, nurses have a high level of preparedness in disaster management. The lack of participation of nurses in disaster volunteers is a serious concern, so it is suggested to the Nursing Division to involve nurses in disaster volunteer both local and national scale disasters.